Modified Cognitive Behavior Therapy for Severe, Treatment‐Resistant Obsessive‐Compulsive Disorder in an Adolescent With Autism Spectrum Disorder. Issue 11 (22nd September 2016) - Krebs, Georgina; Murray, Kim; Jassi, Amita
Abstract : There is a high rate of comorbidity between obsessive‐compulsive disorder (OCD) and autism spectrum disorders (ASD). Standard cognitive‐behavior therapy (CBT) protocols have been shown to be less effective in treating OCD in young people with ASD than in typically developing youth. This case study describes the treatment of an adolescent boy with severe, treatment‐resistant OCD and ASD using a modified CBT approach. Modifications to a standard evidence‐based CBT for OCD protocol included extended psychoeducation about anxiety; regular home‐based sessions; and increased involvement of systems, including family and school. Multi‐informant outcome data indicated significant improvements in OCD symptoms over the course of treatment with gains being maintained over a 12‐month follow‐up period. These findings demonstrate the potential efficacy of modified CBT for pediatric OCD in the context of ASD.